Cystic clear cell papillary renal cell carcinoma: is it related to multilocular clear cell cystic neoplasm of low malignant potential?. Issue 5 (22nd September 2015) - Brimo, Fadi; Atallah, Chantal; Li, Gangyong; Srigley, John R
Abstract : Aims: We report the morphological spectrum of nine cystic clear cell papillary renal cell carcinomas (CCP‐RCC). Methods and results: Mean tumour size was 2.1 cm and the stage was pT1a in all cases. The original diagnosis was multilocular clear cell cystic renal neoplasm of low malignant potential (MCCN‐LMP) in five and CCP‐RCC in four patients. All examples were composed of variably sized cysts lined by one layer of clear cells. Two tumours were exclusively cystic, seven showed tubular formation in the septae and five in which the tubular growth was compact and pseudo‐solid. Two tumours had foci of nests and single cells showing similarities to the cellular areas of MCCN‐LMP. The tubular/pseudo‐solid/nested/single‐cells foci formed microscopic nodules with a mean size of 1.8 mm. Three tumours had intracystic micropapillary formation. Cells were of International Society of Urological Pathology (ISUP) grades 1–2/4. In all cases, the neoplastic nuclei were aligned away from the basement membranes at least focally. Tumours were positive for paired box gene 8 (PAX8), carbonic anhydrase IX (CAIX), cytokeratin (CK)7 and CK34BE12 and negative for CD10. Conclusions: Cystic CCP‐RCC is a pattern that should be recognized, as it shows overlapping morphological features with both multilocular cyst and MCCN‐LMP. This series raises the question of whether some reported MCCN‐LMPs are actually cystic CCP‐RCC.